Pengaruh Likuiditas terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening pada Industri Ritel yang terdaftar di Bursa Efek Indonesia tahun 2019-2023 - Leony Nawa Hoke; I Komang Arthana; Novi Theresia Kiak (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to examine the effect of liquidity on firm value with profitability as an intervening variable in the retail industry listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The sample in this study consisted of 15 retail companies during the period 2019-2023, with a purposive sampling technique. The data used are secondary data obtained from the Indonesia Stock Exchange (IDX) and using the Structural Equation Modeling (SEM) analysis tool with the Partial Least Square (PLS) approach using SmartPLS with the help of SmartPLS 3.0 software. The results of this study indicate that 1) liquidity has a positive and significant effect on firm value. 2) liquidity has a positive and significant effect on profitability. 3) profitability has a positive and significant effect on firm value. 4) profitability mediates the effect of liquidity on firm value.